2018
DOI: 10.1136/bmjopen-2017-018021
|View full text |Cite
|
Sign up to set email alerts
|

Timing of probiotic milk consumption during pregnancy and effects on the incidence of preeclampsia and preterm delivery: a prospective observational cohort study in Norway

Abstract: ObjectivesTo investigate whether the timing of probiotic milk intake before, during early or late pregnancy influences associations with preeclampsia and preterm delivery.DesignPopulation based prospective cohort study.SettingNorway, between 1999 and 2008.Participants70 149 singleton pregnancies resulting in live-born babies from the Norwegian Mother and Child Cohort Study (no chronic disease, answered questionnaires, no placenta previa/cerclage/serious malformation of fetus, first enrolment pregnancy). Only n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 70 publications
(53 reference statements)
2
64
1
5
Order By: Relevance
“…Women in the probiotic group had significantly lower incidence of mastitis [9]. Furthermore, this study differs by evaluating dietary intake during the first half of pregnancy even if it is assumed that the reported habitual intake of probiotic milk products in pregnancy is a proxy of the continued habitual intake during breastfeeding [16,34]. In this epidemiologic setting, the outcome variables were based on the women's self-reported data and their own initiative to use health-care services and not on medical records with International Classification of Disease (ICD) codes or examination performed by health-care professionals, which might have introduced bias as described above regarding level of education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women in the probiotic group had significantly lower incidence of mastitis [9]. Furthermore, this study differs by evaluating dietary intake during the first half of pregnancy even if it is assumed that the reported habitual intake of probiotic milk products in pregnancy is a proxy of the continued habitual intake during breastfeeding [16,34]. In this epidemiologic setting, the outcome variables were based on the women's self-reported data and their own initiative to use health-care services and not on medical records with International Classification of Disease (ICD) codes or examination performed by health-care professionals, which might have introduced bias as described above regarding level of education.…”
Section: Discussionmentioning
confidence: 99%
“…Although pregnancy is a time when most women think a lot about healthy eating, the major changes occur for intake of alcohol and coffee, while their core diet largely remains unchanged [34]. Maternal probiotic milk intake was also asked for in a less comprehensive way in MoBa Q1 and Q3 regarding the time period from before pregnancy to answering Q3 in pregnancy week 32, showing that most women continued to consume probiotic milk products as before pregnancy [16]. Administration of antibiotics, common as prophylaxis in obstetrics, or as treatment for manifest infection, might have interfered with the probiotic effect; this type of datum is not available in the MoBa data set.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Very recently, in a prospective study, Nordqvist et al [192] evaluated the possible relationship among the probiotic milk consumption and the appearance of PTB and preeclampsia incidences. Maternal inflammatory response is a common background of these two pathologic conditions, and the potential anti-inflammatory effect of probiotics represents the criterion for their selection [193,194].…”
Section: Probiotics In Pregnant Womenmentioning
confidence: 99%
“…2,27 The association between intake of probiotic Lactobacilli and reduction in risk of preterm delivery was established in clinical studies. 28,29 Myhre et al, reported that the intake of probiotics reduced the risk of preterm labor by 18% (OR 0.82; 95% CI 0.681-0.986; p = 0.035). However, the study was based on the use of recall questionnaires and there was a lack of clarity in reporting outcomes.…”
Section: Probiotics and Preterm Deliverymentioning
confidence: 99%
“…The authors found that consumption of probiotic product during early pregnancy reduced the risk of preterm delivery by 21% (OR 0.79; CI 0.64-0.97). 29…”
Section: Probiotics and Preterm Deliverymentioning
confidence: 99%